Takaful: Principles and Applications in Managing Death Charity Money Scheme (DCMS) at Tengku Mizan Zainal Abidin Mosque, Kerteh, Terengganu to Develop Ecosystem of Halal Social Economy - Setiyawan Gunardi; Azman Ab. Rahman; Ahmad Zaki Salleh; Khairunneezam Mohd Noor; Syed Mohd Najib Syed Omar; Zawin Hannan Sofea Shahbuddin (International Journal of Religion, 2024)
Non-Indexed Publication